3D visualization ablation planning system assisted microwave ablation for hepatocellular carcinoma (Diameter >3): a precise clinical application - An, Chao (BMC Cancer, 2020)
BACKGROUND: The aim of this retrospective study was to compare the feasibility and efficiency of ultrasound-guided percutaneous microwave ablation (US-PMWA) assisted by three-dimensional visualization ablation planning system (3DVAPS) and conventional 2D planning for hepatocellular carcinoma (HCC) (diameter > 3 cm). METHODS: One hundred thirty patients with 223 HCC nodules (5.0 ± 1.5 cm in diameter, [3.0–10.0 cm]) who met the eligibility criteria divided into 3D and 2D planning group were reviewed from April 2015 to August 2018. Ablation parameters and oncological outcomes were compared, including overall survival (OS), recurrence-free survival (RFS), and local tumor progression (LTP). Multivariate analysis was performed on clinicopathological variables to identify the risk factors for OS and LTP. RESULTS: The median follow-up period was 21 months (range 3–44). Insertion number (5.4 ± 1.2 VS. 4.5 ± 0.9, P = 0.034), ablation time (1249.2 ± 654.2 s VS. 1082.4 ± 584.7 s, P = 0.048), ablation energy (57,000 ± 11,892 J VS. 42,600 ± 10,271 J, P = 0.038) and success rate of first ablation (95.0% VS. 85.7%, P = 0.033) were higher in the 3D planning group compared with those in 2D planning group. There was no statistical difference in OS, and RFS between the two groups (P = 0.995, P = 0.845). LTP rate of 3D planning group was less than that of 2D planning group (16.5% VS 41.2%, P = 0.003). Multivariate analysis showed tumor maximal diameters (P < 0.001), tumor number (P = 0.003) and preoperative TACE (P < 0.001) were predictors for OS and sessions (P = 0.024), a-fetoprotein level (P = 0.004), and preoperative planning (P = 0.002) were predictors for LTP, respectively. CONCLUSIONS: 3DVAPS improves precision of US guided ablation resulting in lower LTP and higher 5 mm-AM for patients with HCC lesions larger than 3 cm in diameter.